Association between levels of blood trace minerals and periodontitis among United States adults - Huang, Handan; Yao, Jingjing; Yang, Nan; Yang, Liuqing; Tao, Lu; Yu, Jinling; Gao, Ying; Liu, Zhihui (Frontiers in Nutrition, 2022)
Aim: Evidence linking trace minerals and periodontitis is very limited. To investigate the relationship between trace minerals (selenium, manganese, lead, cadmium, mercury) and periodontitis, data from the National Health and Nutrition Examination Survey (NHANES) was analyzed after potential confounding factors were taken into account. No known studies have explored the relationship between the five trace minerals and periodontitis. Materials and Methods: 4,964 participants who had undergone a full mouth periodontal examination and laboratory tests of five trace minerals were studied in a cross-sectional study. Clinical attachment loss (CAL) and periodontitis grading were used to measure the severity of periodontitis. Using multivariate linear regression and ordinal logistic regression models, the association between trace minerals and periodontitis was evaluated. Further subgroup analyses were conducted. Results: Blood lead and cadmium were positively associated with mean CAL, blood selenium was negatively associated with mean CAL, but blood mercury, blood manganese and mean CAL were not significantly associated. The association between trace minerals and mean CAL was more significant in males, the elderly, and the diabetics. There was a threshold effect between blood cadmium and mean CAL. Among blacks and people aged over 75, the relationship between blood cadmium and mean CAL followed an inverted U-shaped curve. And there was a saturation effect in the study of blood lead in people aged 45-59. Conclusion: Our study highlighted that blood selenium, blood lead and blood cadmium were significantly associated with periodontitis in a nationally representative sample of US adults.